Ingresos mensuales en odontólogos del Ecuador - Mena-Silva, Paola Andrea; Oñate-Silva, Ana Paulina; Carrión-García, Antony David; Armijos-Briones, Fernando Marcelo (Revista Arbitrada Interdisciplinaria de Ciencias de la Salud. Salud y Vida, 2021)
Ingresos mensuales en odontólogos del Ecuador